Hubungan Sektor Transportasi dan Gross Domestic Product (GDP) Pada Negara Anggota Organisasi Kerjasama Islam (OKI) Dengan Menggunakan Analisis Kausalitas Granger Tahun 1986-2015 - Baiatus Subbaniyah; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to determine the relationship of reciprocity between the transport sector and the GDP on the State member of the OIC. This study uses air transportation of cargo and passengers and GDP using the income calculations. The population in this study is a State member of the OIC, the number of samples used are15 countries in 1986-2015. The analytical method used in this research is by using the Granger Causality. The results showed that there is a reciprocal relationship between the transport sector and the GDP in two OIC member countries, there are Mozambique and Tunisia, and there is a unidirectional relationship in three OIC member countries,there are Egypt. Arab Rep, Pakistan and Saudi Arabia, and also 10 other OIC member countries, there are Bangladesh, Brunei Darussalam, Indonesia, Jordan, Malaysia, Morocco, Sudan, Suriname, Turkey and Uganda there is no relationship between the transport sector and GDP.